Adsorption and Photocatalytic Kinetics of Visible-Light Response N-Doped TiO2 Nanocatalyst for Indoor Acetaldehyde Removal under Dark and Light Conditions - Yu-Hao Lin; Chih-Huang Weng; Jing-Hua Tzeng; Yao-Tung Lin (International Journal of Photoenergy)
Understanding the removal nature of the indoor volatile organic compounds under realistic environment conditions would give clear guidance for the development of air purification devices. The study investigated the removal of indoor acetaldehyde using visible-light-responsive N-doped TiO2 (N-TiO2) photocatalyst under visible-light irradiation (light) and in the absence of light (dark). The adsorption kinetics of acetaldehyde onto N-TiO2 followed a pseudo-second-order model. The magnitude of acetaldehyde adsorption is proportional to temperature, and the results were fitted to the Langmuir isotherm model. Moreover, the effect of initial acetaldehyde concentration and visible-light intensity on the photooxidation of acetaldehyde was well described by the Langmuir-Hinshelwood model. Results show that the mesoporous N-TiO2 catalyst had a high ability to absorb acetaldehyde in the dark condition, and then acetaldehyde was subsequently photooxidized under visible-light irradiation. The adsorption capacity was found to increase with decreasing temperature. The negative value of ΔG° and the positive value of ΔS° indicate that the adsorption of acetaldehyde onto N-TiO2 was a spontaneous process. Finally, a reaction scheme for removal process of indoor acetaldehyde by N-TiO2 was proposed.